2004
DOI: 10.1093/jxb/erh002
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic variation in the shoot mineral concentration of angiosperms

Abstract: The calcium (Ca) concentration of plant shoot tissues varies systematically between angiosperm orders. The phylogenetic variation in the shoot concentration of other mineral nutrients has not yet been described at an ordinal level. The aims of this study were (1) to quantify the shoot mineral concentration of different angiosperm orders, (2) to partition the phylogenetic variation in shoot mineral concentration between and within orders, (3) to determine if the shoot concentration of different minerals are cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
211
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(240 citation statements)
references
References 18 publications
21
211
3
1
Order By: Relevance
“…Literature reports of inter-species comparisons in Sr concentrations of any isotope were compiled with data we generated for 85 Sr using the Residual Maximum Likelihood (REML) procedure of Broadley et al ( , 2001Broadley et al ( , 2003Broadley et al ( , 2004. Nine publications were identified that reported, without the possibility of foliar contamination, a comparison of concentrations of a Sr isotope in green shoots in two or more plant species growing on the same substrate under identical conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports of inter-species comparisons in Sr concentrations of any isotope were compiled with data we generated for 85 Sr using the Residual Maximum Likelihood (REML) procedure of Broadley et al ( , 2001Broadley et al ( , 2003Broadley et al ( , 2004. Nine publications were identified that reported, without the possibility of foliar contamination, a comparison of concentrations of a Sr isotope in green shoots in two or more plant species growing on the same substrate under identical conditions.…”
Section: Methodsmentioning
confidence: 99%
“…REML analysis was run on the statistical package Genstat for Windows 5th Ed. release 4.2 (VSN International, Oxford, UK) (Thompson and Welham, 2001) using the programme of Broadley et al ( , 2001Broadley et al ( , 2003Broadley et al ( , 2004. Defining blocks and treatments in this way accounts for the absolute differences in values arising from blocks (experimental conditions) to reveal mean relative values for the treatments (species).…”
Section: Methodsmentioning
confidence: 99%
“…The above relationship was also showed by the results of other studies concerning quality wheat (Gaj 2010(Gaj , 2013. The mechanism of interaction between N and K as well as N and P has been well documented in subject literature (Marschner, et al, 1996;Greenwood and Stone 1998;Broadley, et al, 2004). Uptake of nitrate ions, and then their transport in plants in fact depends on supply of K and requires constant delivery of this nutrient.…”
Section: Methodsmentioning
confidence: 56%
“…In addition to physiological constraints, tissue concentrations of Ca, Mg and K differ markedly between equivalent tissues of plant species growing in the same environment due to evolutionary factors (18,19,(24)(25)(26) . For example, a considerable proportion of the genetic variation in shoot Ca and Mg, and to a lesser extent K, concentrations occurs at the family level or above.…”
Section: Why Do Crop Plants Differ In Calcium Magnesium and Potassiumentioning
confidence: 99%